1989
DOI: 10.1007/bf00558498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term omeprazole administration of serum pepsinogens in relation to fasting serum gastrin and gastric acid secretion

Abstract: A study has been done in 10 male healthy volunteers of the effect of oral omeprazole 20 mg daily for 3 days on the serum concentrations of Pepsinogens A and C in relation to changes in fasting serum gastrin and basal and pentagastrin stimulated gastric acid output. The concentrations of Pepsinogens A and C showed concomitant and variable but significant increases, and the Pepsinogen A, C ratio did not change during the 3-day course of omeprazole. The increments were also significantly correlated with the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Serum pepsinogen I levels are reported to rise after administration of omeprazole or other proton pump inhibitors, both after short and long‐term treatment 47 –50 . This study showed somewhat lower serum pepsinogen I in the wild type/mutated group of patients compared to wild type/wild type group.…”
Section: Discussionmentioning
confidence: 55%
“…Serum pepsinogen I levels are reported to rise after administration of omeprazole or other proton pump inhibitors, both after short and long‐term treatment 47 –50 . This study showed somewhat lower serum pepsinogen I in the wild type/mutated group of patients compared to wild type/wild type group.…”
Section: Discussionmentioning
confidence: 55%
“…As renal clearance of pepsinogens is not inhibited by omeprazole [8,19], it has been suggested that omeprazole directly [7] or indirectly increases the concentrations of pepsinogens in the gastric glands, which results in an enhanced back diffusion of pepsinogens from gastric mucosa into the systemic circu lation [8,10]. Studies on isolated guinea pig fundic mucosa [20] and isolated rabbit chief cells [21].…”
Section: Discussionmentioning
confidence: 99%
“…1993 nogen C. previously called pepsinogen I and II. Pepsi nogen A is secreted by the chief cells in the gastric fundic mucosa only [5], Unlike pepsinogen A, pepsinogen C is secreted by both fundic and antral mucosa and also in the proximal duodenum [6], It is reported that short-term administration of omeprazole in unoperated subjects in creases both serum gastrin and serum pepsinogen A and pepsinogen C levels [7][8][9][10]. Long-term maintenance ther-J.L.…”
mentioning
confidence: 99%
“…There was no significant difference between the two separate pre-entry studies of 24 hour pH (median (interquartile range), 1-45 (1-2-1-9) and 1 40 (1 2-2 0)). The median 24 Omeprazole was administered as enteric coated granules in hard gelatin capsules each containing 20 mg or the equivalent of placebo. The daily dose was two capsules, either two times omeprazole 20 mg (40 mg) or one capsule omeprazole 20 mg and one placebo.…”
Section: Intragastric Phmentioning
confidence: 99%
“…These comprehensive studies were performed in healthy volunteers because it has been shown that the effects of weekend treatment with 20 mg omeprazole on gastric acid and serum gastrin are comparable in healthy subjects and duodenal ulcer patients. '8'920 Since it has been shown that weekend therapy with 20 mg omeprazole induces transient increases in serum pepsino- 24 gens, we also measured serum pepsinogen A and C and their ratio. To obtain steady state conditions with the weekend doses the investigations did not begin until the third week of treatment.…”
mentioning
confidence: 99%